China and India Learning from Each Other : Reforms and Policies for Sustained Growth - Prasad, Eswar (International Monetary Fund, 2006)
What does the future hold for these giants that are two fastest-growing emerging markets and among the three largest economies in Asia? Their economic muscle is having increasingly far-reaching effects on the global economy. This must-read book draws together analysis and insight from high-level policymakers and advisors in both countries and shows how, for many years, the two countries have cooperated and learned from each other. In addition, the book describes what has (and what has not) worked in each country and offers some concrete suggestions about how each may achieve long-term sustainable development.